Tracking intentionalism and the phenomenology of mental effort. - Doulatova, Maria (Synthese, 2021)
Most of us are familiar with the phenomenology of mental effort accompanying cognitively demanding tasks, like focusing on the next chess move or performing lengthy mental arithmetic. In this paper, I argue that phenomenology of mental effort poses a novel counterexample to tracking intentionalism, the view that phenomenal consciousness is a matter of tracking features of one's environment in a certain way. I argue that an increase in the phenomenology of mental effort does not accompany a change in any of the following candidate representational contents: (a) representation of externally presented features, e.g. brightness, contrast, and so on (b) representation of task difficulty, (c) representation of the possibility of error, (d) representation of trying to achieve some state of affairs, (e) representation of bodily changes like muscle tension, or (f) representation of change in cognitive resource availability and lost opportunity cost. While tracking intentionalism about some phenomenal experiences like pains might obtain, it does not seem to obtain for all phenomenal experiences. This puts the intentionalist into an uncomfortable position of trying to explain why some phenomenal experiences have representational content and not others. Since many believe that tracking intentionalism or something like it provides the best chance of naturalizing consciousness, these arguments deserve detailed consideration.